Surgical Management of Multiple Cerebral Hydatid Cysts without Systemic Involvement: A Case Report - Roxana Radu; Miguel Azevedo; Angela Neacșu; Marius Cristian Zaharia; Radu Mircea Gorgan (Brazilian Neurosurgery)
Hydatidosis is a rare and serious parasitic disease caused by Echinococcus granulosus larvae, with central nervous system (CNS) involvement being a potentially fatal complication. We present a case of neurohydatidosis in a 55-year-old male farmer exhibiting symptoms of the left parietal syndrome. Imaging studies revealed six well-defined, non-enhancing cystic lesions in the left parietal lobe, and serological evaluation confirmed the presence of Echinococcus-specific IgG antibodies. A chest-abdomen-pelvis CT scan showed no additional hydatid cysts in other organs.